The Notary as a Digital Mediator is Not a Degradation of the Notary's Function - Pangestu, Dimas Aditya (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Dispute resolution in Indonesian law is carried out in two ways, namely litigation settlement and alternative dispute resolution or out of court. In the course of their duties, notaries often to act as mediators before the disputing parties. However, for deep and substantial dispute resolution, the notary is not a party the authority to give a decision or sentence. It is the judge or certified mediator who is authorized to give a decision or sentence on a legal dispute. A notary's duties in dispute resolution are limited to witnessing and certifying documents. These duties are currently facilitated by technological developments, namely through the e-notary, e-signature and certification authority systems. The digitalisation of notaries certainly facilitates the work of notaries, but it does not mean reducing the functions of existing notaries.